2014
DOI: 10.1063/1.4898346
|View full text |Cite|
|
Sign up to set email alerts
|

Quasi-Fermi level splitting and sub-bandgap absorptivity from semiconductor photoluminescence

Abstract: A unified model for the direct gap absorption coefficient (band-edge and sub-bandgap) is developed that encompasses the functional forms of the Urbach, Thomas-Fermi, screened Thomas-Fermi, and Franz-Keldysh models of sub-bandgap absorption as specific cases. We combine this model of absorption with an occupation-corrected non-equilibrium Planck law for the spontaneous emission of photons to yield a model of photoluminescence (PL) with broad applicability to band-band photoluminescence from intrinsic, heavily d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
165
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(171 citation statements)
references
References 45 publications
6
165
0
Order By: Relevance
“…The similar absorption phenomenon has been observed in the previous literature, but the reasons remain undiscussed25. It is reported that the model of sub-bandgap absorption can also be applied to the fitting of room temperature PL2426. When a p-n junction is established, the built-in internal electric field will lead to band bending, the p-n junction can emit the light which energy is smaller than the bandgaps of n-type and p-type materials.…”
Section: Resultssupporting
confidence: 64%
“…The similar absorption phenomenon has been observed in the previous literature, but the reasons remain undiscussed25. It is reported that the model of sub-bandgap absorption can also be applied to the fitting of room temperature PL2426. When a p-n junction is established, the built-in internal electric field will lead to band bending, the p-n junction can emit the light which energy is smaller than the bandgaps of n-type and p-type materials.…”
Section: Resultssupporting
confidence: 64%
“…The result plotted in Figure 3d reveals a step function-like CT state absorption spectrum in the range 1-1.6 eV that is clearly different from the Gaussian lineshape observed for other localized CT excitations using this same method. In this context, we applied a 2D DOS direct bandgap model [31] to the EL and polarized EQE subtraction data of the crystal PHJ device (see the Supporting Information for model details). In this context, we applied a 2D DOS direct bandgap model [31] to the EL and polarized EQE subtraction data of the crystal PHJ device (see the Supporting Information for model details).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we applied a 2D DOS direct bandgap model [31] to the EL and polarized EQE subtraction data of the crystal PHJ device (see the Supporting Information for model details). Compared with a CuZnSnSSe solar cell, [31] the crystal PHJ device has a ≈20% smaller energy broadening parameter, γ, underscoring the narrowness of its emission peak as a result of the highly ordered system. Compared with a CuZnSnSSe solar cell, [31] the crystal PHJ device has a ≈20% smaller energy broadening parameter, γ, underscoring the narrowness of its emission peak as a result of the highly ordered system.…”
Section: Resultsmentioning
confidence: 99%
“…1) and α 0 is a proportionality constant, has also been proposed for heavily doped semiconductors [22]. This model gave a better fit to the EQE data ( Fig.…”
Section: Experimental Methodsmentioning
confidence: 98%